Redesign of Residential Catalogue Websites with a Personal Extreme Programming Approach to Improve User Experience Satisfaction (Case Study: PT CBS Land Indonesia) - Putri Faza Aulia; Anita Safitri (Universitas Negeri Surabaya, 2025)
The property business always attracts the attention of many people, encouraging business people to compete to improve their business. One way is to use technology as an effective promotional tool to develop a business. This research involves the creation of a catalog-based website promotion system that assists PT. CBS Land Indonesia in promoting its business. The existence of this promotion system can ease the company's efforts in promoting properties to potential customers in an integrated manner. This system uses the CodeIgniter framework and employs the Personal Extreme Programming (PXP) method for website development, while website testing is conducted using black box testing and website testing is done using blackbox testing with the aim of knowing user satisfaction which is measured by increasing using SUS indicators. During Blackbox testing, the functionality of the housing catalog website is evaluated to ensure it meets user expectations. Meanwhile, the measurement of user satisfaction improvement is conducted by providing a questionnaire with SUS indicators to website users before the redesign is carried out. The result of this research is a catalog website design with various new features that PT. CBS Land Indonesia can use to reach a broader market. In conclusion, this research develops a catalog-based website promotion system for PT. CBS Land Indonesia, aimed at facilitating property promotion to potential customers. This system is built using the CodeIgniter framework and the Personal Extreme Programming (PXP) method, and a questionnaire with the System Usability Scale (SUS) indicator is used to measure the extent to which user experience satisfaction has increased.